Моделирование свойств CdZnTe и параметров детекторов γ-излучения на его основе - Kondrik, A. I. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
By means of computer modeling, the carrier lifetime and mobility, as well as the resistivity of CdxZn1–xTe:Cl material, were investigated in order to determine the optimal combination of these properties and the molar fraction of CdTe that would provide maximum charge collection efficiency in γ-radiation detectors based on this material. A typical impurity composition, independent of the preparation method, was taken as the starting point. It is shown that the studied material must be inhomogeneous, and an approximate distribution of its properties in the interelectrode space of the detector has been established.